Perilaku Pemustaka dalam Telusur Informasi di Perpustakaan Pascasarjana Universitas Negeri Padang - Putri, Dini Olifia; Ardoni, Ardoni (Universitas Negeri Padang, 2020)
AbstractIn this paper discussed about information seeking behavior of library users of the State University of Padang Postgraduate Library because of a lack of knowledge in finding the information they need precisely and quickly. Because not a few postgraduate users who feel confused in finding the information needed. This research question covers how post-market visitors' information seeking behavior encompasses the stages of their activities. The purpose of writing this paper is to describe the behavior of information retrieval of postgraduate library students at Padang State University. The method of data collection is carried out on librarians and librarians through observation, interviews, and library studies in the Postgraduate Library of Padang State University. Analyzing data is done descriptively.Based on analyzing the data, it was concluded that in searching for library information in the Postgraduate Library of Padang State University there are two stages, namely: (1) behavior of the user when searching for information with the user strategy in information retrieval, which includes: starting, browsing, and extracting, (2) meanwhile, the technique of searching information on librarians in the Postgraduate Library of Padang State University shows that in conducting information search, library users use information search techniques based on words and information search techniques based on the closest words.Keywords: optimization, competence, electronic archives.